Implementasi Pendidikan Karakter dengan Pendekatan Holistik di SMK - Regita Wela Agustin; Titik Ulfatun (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to identify character values, understand the implementation of character education, and identify challenges in implementing character education for students at SMK Tunas Harapan 2 Mondokan with a holistic approach. The study is qualitative, employing data collection techniques such as interviews, observations, and documentation. The participants include the school principal, vice principal, guidance counselor, class teachers, and students at SMK Tunas Harapan 2 Mondokan. Data analysis involves data reduction, presentation, and verification. To ensure data validity, the research applies the triangulation method. The research findings reveal that character values implemented at SMK Tunas Harapan 2 Mondokan encompass aspects such as religiosity, honesty, tolerance, discipline, creativity, independence, love, peace, environmental concern, social awareness, and responsibility. The implementation of character education is integrated into the school's vision and mission, involving learning activities in all subjects, extracurricular activities, and collaboration with parents and the community. Challenges in implementation are identified from family and social environment factors, highlighting difficulties in shaping the holistic personality of students in the educational setting. These findings provide insights into the contribution and complexity of managing character education aspects at SMK Tunas Harapan 2 Mondokan.